Length-weight relationship of bigeye scad, Selar crumenophthalmus (Bloch, 1793): Regular vs hierarchical bayesian methods - BG Hutubessy; VPY Likumahuwa; JW Mosse (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
Fisheries management or conservation requires information on length-weight relationship (LWR) for the fishing regulation and biomass estimation. This study aims to assess LWR estimation using two methods, regular and Bayesian hierarchical approached for big-eye Scad (Selar crumenophthalmus). Samples of big eye Scad were collected at several fish landings around Ambon Island from March to August 2020. Length-weight relationship measurement to obtain the parameters of W = a*Lb was tested using generalized linear model and t-test. The parameter b for monthly sampling was not significantly different (F = 0.77, df = 70, P = 0.89) and showed isometric growth b=3 (t = -1.13, df = 4, P = 0.32). Regular measurement resulted parameter log10(a) = -1.99 (±SD = 1.06) dan b = 3.06 (±SD = 0.084). Bayesian method produced parameter log10(a) = -2.07 (±SD = 0.2365) dan parameter b = 3.21 (±SD = 0.1497). Weight measurement from HB approach was significantly higher than the regular method (t = 1.65; df = 405; P <0.0001), and might produce over-estimated of weight from length data. Discrepancy of these methods was overcome by combining all information of LWR to obtain the best estimation on LWR parameters. Abstrak Pengelolaan perikanan atau konservasi memerlukan informasi tentang bobot ikan untuk estimasi biomassa dan regulasi penangkapan. Tujuan penelitian ini adalah untuk membandingkan hubungan panjang-bobot hasil pendekatan hirarki bayesian dengan pengukuran regresi langsung ikan selar bentong, Selar crumenophthalmus. Ikan selar bentong dikoleksi dari lima tempat pendaratan ikan di Pulau Ambon dari bulan Maret hingga Agustus 2020. Pengukuran panjang total dan bobot ikan selar bentong bertujuan untuk memperoleh hubungan panjang-bobot dengan formulasi W = a*Lb. Uji general linear model dipakai untuk menguji parameter b (kemiringan) pada bulan pengamatan yang berbeda. Uji-t satu sampel dipakai untuk menguji pertumbuhan isometrik (b=3). Hasil penghitungan hubungan panjang-bobot berdasarkan pengukuran langsung dibandingkan dengan hasil estimasi dengan pendekatan bayesian dan diuji dengan uji-t. Nilai parameter b dari pengamatan langsung tidak berbeda untuk bulan pengamatan (F = 0,77, df = 70, P = 0,89) dan ikan selar memiliki pola pertumbuhan isometrik, b=3 (t = -1,13, df = 4, P = 0,32). Pengukuran regresi langsung memperoleh parameter log10(a) = -1,99 (±sb = 1,06) dan b = 3,06 (±sb = 0,084). Metode Bayesian menghasilkan parameter log10(a) = -2,07 (±sb = 0,2365) dan parameter b = 3,21 (±sb = 0,1497). Estimasi bobot dengan pendekatan bayesian terlalu tinggi (t = 1,65; df = 405; P < 0,0001), memungkinkan timbulnya bias pada pendugaan biomassa. Hasil ini berarti metode bayesian adalah over estimasi, sehingga perlu banyak data dan info yang digabung untuk menekan bias dalam mengestimasi hubungan panjang-bobot dan biomassa.